Towards a Self-Reliance of Small and Medium Tourism Industry in 2040: How Bali’s Government Makes Efforts? - Suyatna, I Nyoman; Sudiarta, I Ketut; Satyawati, Ni Gusti Ayu Dyah (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 10 No 4 (2021)DO - 10.24843/JMHU.2021.v10.i04.p01, 2021)
Bali Provincial Regulation No. 8 of 2020 concerning Bali Province Industrial Development Plan Year 2020-2040 was created to balance the structure and fundamentals of the Balinese economy which includes three pillars, namely tourism, agriculture, and industry. Besides, it also reflects an effort to reduce the dependence of the Balinese economy on tourism.   This article assesses the process of the creation of Bali Provincial Regulation No.8 of 2020 concerning Bali Province Industrial Development Plan Year 2020-2040 and its content, mainly regarding the position of the small and medium tourism industry. It also offers a lens on the future legal framework of the tourism industry in Bali. It is a normative legal study that uses the statute, conceptual, and analytical approaches. This article argues that the future legal framework of the tourism industry should deal with, at least, the following five issues: mass tourism; degradation of nature and environmental quality; meeting the perception and expectation of travelers; the quality of  tourism services; and protection to the tourists as a costumer.